Analysis of Optical Losses in a Photoelectrochemical Cell: A Tool for Precise Absorptance Estimation. (20th November 2017) - Cendula, Peter; Steier, Ludmilla; Losio, Paolo A.; Grätzel, Michael; Schumacher, Jürgen O.
Abstract: Optical losses in a photoelectrochemical (PEC) cell account for a substantial part of solar‐to‐hydrogen conversion losses, but limited attention is paid to the detailed investigation of optical losses in PEC cells. In this work, an optical model of combined coherent and incoherent light propagation in all layers of the PEC cell based on spectroscopic measurements is presented. Specifically, photoelectrodes using transparent conductive substrates such as F:SnO2 coated with thin absorber films are focused. The optical model is verified for hematite photoanodes fabricated by atomic layer deposition and successfully used to determine wavelength‐dependent reflection, transmission, layer absorptances, and charge generation rates. Furthermore, the calculated absorptances enable 20–30% more accurate calculations of the absorbed photon‐to‐current efficiency of PEC cells. Our optical model is a powerful tool for the optimization of the optical performance of PEC cells focusing on single absorber or tandem configurations and represents a cornerstone of a complete (optical and electrical) model for PEC water splitting cells. Abstract : An in‐depth analysis of wavelength‐dependent optical losses for a photoelectrochemical water splitting cell based on a transparent conducting substrate is presented. Specifically, ultrathin films with a thickness comparable to the roughness of the substrate are described conveniently with the graded layer approach. Our validated model enables extraction of absorptance and absorbed photon‐to‐current efficiency of the photoabsorber with improved accuracy over established methods.